The degree of availability of administrative excellence standards among school principals at Tafila Governorate from the teachers’ perspectives - Alkriameen, Hani Ahmad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree of availability of administrative excellence standards among school principals at Tafila Governorate from the teachers’ perspective, according to the variables: sex, educational qualification, and experience. The study sample consisted of 283 male and female teachers, the results of the study showed that the degree of availability of administrative excellence standards among school principals was mid (average= 3.19), the standard of professional ethics had the highest average (3.25), then the standard of scientific mastery and professional development with an average of (3.24), communication with the local community (3.21), leadership of supervisory operations (3.17), and finally creative initiatives (3.12), the results also showed statistically significant differences in teachers’ viewpoints attributed to the sex of the teacher in favor of the female teachers, and there were no statistically significant differences in teachers’ perspectives attributed to the experience or academic qualification. Based on the results, the researcher recommends the adoption of administrative excellence standards in training programs for school principals, directing workers in the directorates of education to adhere to administrative excellence standards in the professional development of principals. The researcher also suggested complementary studies on the subject.